Spatiotemporal variation in urban wastewater pollution impacts on river microbiomes and associated hazards in the Akaki Catchment, Addis Ababa, Ethiopia - Hiruy, A.M.; Mohammed, J.; Haileselassie, M. M.; Acharya, K.; Butte, G.; Haile, Alemseged Tamiru; Walsh, C.; Werner, D. (Elsevier, 2022)
In Addis Ababa and its environs, most urban wastewater is discharged into rivers without treatment. This study related urban wastewater characteristics to the prevalence of faecal, antibiotic resistant, and potentially pathogenic bacteria in rivers of the Akaki catchment across six locations, for the dry and wet season. Spatiotemporal variation in bacterial hazards across the catchment was up to 6 log10 units. Cooccurrence of sewage pollution marker gene HF183 in all river samples testing positive for the Vibrio cholerae marker gene ompW, and high levels of these two genes in untreated wastewater, identified human sewage as the likely source of Vibrio cholerae hazards in the catchment. Levels of the marker genes rodA for E. coli, HF183 for human host associated Bacteroides, ciaB for Arcobacter, and ompW for Vibrio cholerae were all higher in the dry season than in the wet season. Marker gene gyrB for Pseudomonas aeruginosa was not detected in the samples. From the sequencing data, notable bacterial genera in the dry season included wastewater pollution indicators Arcobacter and Aeromonas, whereas soil erosion may explain the greater prominence of Legionella, Vicinamibacter, and Sphingomonas during the wet season. Except for the most upstream location, all faecal coliform (FC) counts exceeded WHO standards of 1000 CFU/100 mL for unrestricted irrigation. Concerningly, 0.6–20% of FC had ESBL producing antimicrobial resistance traits. In conclusion, multiple bacterial hazards were of concern for river water users in the Akaki catchment, and elevated in the dry season, when the river water is being used for irrigation of vegetable fields that supply the markets of Addis Ababa. This reflects inadequate treatment and limited dilution of urban wastewater by the natural river flows during periods of low rainfall.